Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 6 The results obtained show that the average canteen dinner is a good one, containing, as it should, an energy value of about 1,000 calories, well distributed among the amounts of protein, fat, and carbohydrate. Apart from calorie value, inspection of the dinners showed that meat, vegetables, and puddings were made of good materials and well cooked. For the relief of monotony, an important factor in connection with industrial canteens, a change of surroundings during the meal and a short walk before partaking of it are desirable. On this account, and also on account of the importance of ventilating the workshop so that the air may be fresh when the workers return, the custom of eating meals within the workshop should be discontinued, and all food should be taken, whether in a canteen, restaurant, in the open air, or at least away from the ordinary place of work. 9. Food brought by Workers.— The next subject investigated was the nature and energy value of meals brought by workers from their own homes. Many workers who bring their own food often supplement it by purchasing sweets, cake or fruit, and by taking tea or drinking mineral waters. Even where there is no canteen established, facilities are often provided for heating carried food and for supplying hot water to make tea ; and there may be places where sweets, cakes, chocolates, mineral waters, and sometimes fresh fruit can be purchased. The workers from whom meals for analysis were obtained were not asked beforehand to bring a sample meal, but were interrogated at the entrance gate and asked if they would exchange the contents of their dinner-basket for a sum ample to buy a meal at the canteen. The following results were obtained :— (1) Meal brought from home by man on night shift— Rabbit and vegetables in basin. Protein 28.9 grammes 683.4 calories. Fat 7.6 grammes Carbohydrate 120.8 grammes This meal contained no pudding or other sweet, so probably the owner meant to supplement it by minor purchases at the canteen. (2) Meal brought from home by man on night shift— Sausage roll ; bread and butter and ham ; and cheese. Protein 36.2 grammes 1,448 calories. Fat 58.2 grammes Carbohydrate 160.5 grammes (3) Meal brought from home by boy, aged about 15, on night shift— Dish of potatoes, tomatoes and bacon; jam puff; a cake; bread and butter and jam. Protein 31.7 grammes 1,719 calories. Fat 61.4 grammes Carbohydrate 248.3 grammes These meals may be compared with the meal supplied by canteen of the factory (No. 1 in Table I). The boy's meal with its 1,719 calories as contrasted with the 1,346 of the canteen meal, or with the 1,448 of the man, illustrates the effect of growth and work in producing appetite, but, even after allowance is made for growth, it is probably excessive. 10. Food of Women Workers.— The dietaries of women-workers were next examined ; and in Table II the energy value of food obtained from women's restaurants, from a works canteen, and from workers is contrasted. The meal from restaurant No. 1 is a sensible meal supplied at small cost, but that from restaurant No. 2 is an example of the unsatisfying meals which pale-faced young women may often be seen consuming in popular cafés. In considering the canteen meals a portion of sweet should be added to each meat dish ; the meal then totals up to between 500 and 700 calories of energy value. Unless somewhat larger meals are eaten at home, this is too near the minimum required for girls working long hours and travelling considerable distances to and from work. Each of the three normal meals of an average working man should contain 1,000 calories, as eaten, and of a working woman 0.8 to 0.9 of this amount ; that is, from 800 to 900 calories. 11. Girls who bring their own dinner often buy in addition a portion of pudding or cake from the canteen, and the analyses show that this portion adds from 150 to 300 calories to the meal. The food brought from home varies greatly in nutritive value from 295 to 1,143 calories ; while the latter is sufficient without anything from the canteen, the former could scarcely be made enough even if a double helping of pudding were added. Whether deficiencies in the meal taken during the working period are made up by more liberal meals at home, or whether these meals also are deficient, could not be ascertained ; but even if the home meals are more liberal the distribution of the day's eating is on wrong lines ; for in a long day's work, say of 12 hours, there should be a good meal in the longest break, if the efficiency of the worker is to be maintained for months and years. Experience, however, indicates that for a large class of workers home meals are hurried, and, especially for women-workers, too often consist or bread and boiled tea. A worker starting the day with a bread and tea breakfast, and walking or travelling for an hour or more to work, cannot remain for long an efficient worker ; and probably much broken time and illness arise from this cause. 127/NU/5/5/1/1